Efeitos quânticos devido a quebra da simetria de Lorentz produzida por campos vetoriais de fundo e campos elétricos - Oliveira, Adriano dos Santos (2022)
The main objective of this thesis is to study relativistic and non-relativistic quantum effects on the dynamics of a spin-half particle, neutral or electrically charged, interacting with electric fields in the presence of fixed background fields that give a preferential direction in space-time . Thus violating the Lorentz symmetry. From the insertion of a non-minimum coupling in the Dirac equation, it is possible to describe the interaction of the spin-half particle with electric fields in the Lorentz symmetry violation background and with that, obtain the energy spectrum in various systems. Characterized by analogues of relativistic Landau quantization, Aharonov-Bohm effect, inverse attractive square potential, harmonic oscillator and coulomb potential, where these analogues are studied for a neutral particle. Finally, we study the dynamics of an electron in a Lorentz symmetry violation scenario.